Serum cardiac troponin T after repeated endurance exercise events - Bonetti, A.; Tirelli, F.; Albertini, R.; Monica, C.; Monica, M.; Tredici, G. (International Journal of Sports Medicine, 1996)
Recently Dr. Rowe made a hypothesis according to which small areas of myocardial necrosis can be caused by microvascular spasm, related to high catecholamine concentrations and other mechanisms, following extraordinary unremitting endurance exercises or due to the cumulative effect of several endurance events. It was this last suggestion which prompted us to investigate 25 top cyclists, taking part in the 77th Giro d'Italia. Blood samples were obtained the day before the start of the competition and once a week thereafter until the end. We measured myoglobin, lactic dehydrogenase, total creatine kinase, creatine kinase isoenzyme MB and serum cardiac troponin T (Tn-T), a highly sensitive and specific method for the detection of myocardial injury. While at measuring time points which followed we found a significant increase in the serum indicators of muscle damage, compared with their values at the beginning of the race, creatine kinase isoenzyme MB did not rise significantly and cardiac Tn-T was found in the serum of only 5 athletes, repeatedly in some cases, but always below the cut off values considered as indicating myocardial ischemia. On the basis of the behaviour of creatine kinase isoenzyme MB and, above all, of cardiac Tn-T, we can conclude that heavy endurance exercises, repeated daily for 22 days, as was the case in our study, do not seem able to produce, in top athletes, permanent heart damage by means of acute myocardial injury.